Mapping magnetic field lines between the Sun and Earth. Issue 2 (8th February 2016) - Li, B.; Cairns, Iver H.; Gosling, J. T.; Steward, G.; Francis, M.; Neudegg, D.; Schulte in den Bäumen, H.; Player, P. R.; Milne, A. R.
Abstract: Magnetic field topologies between the Sun and Earth are important for the connectivity to Earth of solar suprathermal particles, e.g., solar energetic particles and beam electrons in type III solar radio bursts. An approach is developed for mapping large‐scale magnetic field lines near the solar equatorial plane, using near‐Earth observations and a solar wind model with nonzero azimuthal magnetic field at the source surface. Unlike Parker's spiral model, which restricts the in‐ecliptic angle Φ B in the Geocentric Solar Ecliptic coordinates to (90°–180°, 270°–360°) and so is unable to predict field configurations for the other Φ B values frequently observed in the solar wind, our approach can account for all the observed Φ B values. A set of predicted maps shows that near both minimal and maximal solar activity the field lines are typically open and that loops with both ends either connected to or disconnected from the Sun are relatively rare. The open field lines, nonetheless, often do not closely follow the Parker spiral, being less or more tightly wound, or strongly azimuthally or radially oriented, or inverted. The time‐varying classes, e.g., bidirectional electrons, of suprathermal electron pitch angle distributions (PADs) at 1 AU are predicted from the mapped field line configurations and compared with Wind observations for two solar rotations, one each near solar minimum and solar maximum. PAD predictions by our approach agree quantitatively (≈90%) with the PAD observations and outperform (by ≈20%) PAD predictions using Parker's model. Key Points: Approach is developed for mapping large‐scale magnetic field lines between the Sun and Earth Mapped field lines mostly are open yet often not closely Parker spiral‐like, e.g., with inversions Approach outperforms Parker's spiral model in predicting observed suprathermal electron PAD classes